Behavioural differences across contexts may indicate morph-specific strategies in the lizard Ctenophorus decresii. (January 2016) - Yewers, Madeleine St Clair; Pryke, Sarah; Stuart-Fox, Devi
Abstract : Discrete colour polymorphisms are often genetically correlated with other traits under natural and sexual selection, such as behaviour, life history and physiology. Elucidating such correlations is essential to understand the adoption of alternative strategies between morphs and the role they play in the maintenance of colour polymorphisms within a population. Using field experiments, we tested the hypothesis that four visually discrete morphs (orange, yellow, yellow with a central orange patch (orange-yellow) and grey) of the tawny dragon lizard, Ctenophorus decresii, display alternative behavioural strategies. Specifically, we compared the response of colour morphs to simulated conspecific territorial intruders and predators in the wild. Although the orange-yellow morph can be objectively classified, it may behaviourally resemble the orange or yellow morph; therefore we compared statistical models in which the orange-yellow morph was considered a separate morph (four-morph model) or grouped with either pure orange or pure yellow individuals (three-morph models). For aggression, a three-morph model with orange-yellow individuals grouped as yellow morphs best fitted the data. The orange morph showed consistently high aggression to all morphs, while the grey morph showed consistently low aggression. Aggression of the yellow morph was conditional on the morph of the intruder. In addition to being the least aggressive, the grey morph was the least bold. Although the orange morph was the most aggressive, it was only the boldest under a three-morph model, which was equally likely compared to a four-morph model. Overall our results support the view that tawny dragon lizard morphs adopt different behavioural strategies, the orange and grey morphs exhibiting more aggressive and cautious strategies, respectively, and the yellow morph changing its aggression depending on its competitor's colour. Highlights: We tested for differences in behaviour of male tawny dragon colour morphs. Morphs consistently differ in conspecific aggressive and antipredator behaviours. Alternative strategies may maintain colour polymorphism in this species.